2020
DOI: 10.3390/polym12112754
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Applications of Smart Piezoelectric Materials for Medical Devices

Abstract: Smart piezoelectric materials are of great interest due to their unique properties. Piezoelectric materials can transform mechanical energy into electricity and vice versa. There are mono and polycrystals (piezoceramics), polymers, and composites in the group of piezoelectric materials. Recent years show progress in the applications of piezoelectric materials in biomedical devices due to their biocompatibility and biodegradability. Medical devices such as actuators and sensors, energy harvesting devices, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 182 publications
0
71
0
Order By: Relevance
“…There are various types of commercially available electrospun scaffolds with specific directions of applications. The most commercially used scaffolds are, e.g., TissueMend R (USA), PolyTape R (Japan), OrthAdapt (USA) and many others [122,123].…”
Section: Electrospun Scaffolds Dedicated To Tissue Engineeringmentioning
confidence: 99%
“…There are various types of commercially available electrospun scaffolds with specific directions of applications. The most commercially used scaffolds are, e.g., TissueMend R (USA), PolyTape R (Japan), OrthAdapt (USA) and many others [122,123].…”
Section: Electrospun Scaffolds Dedicated To Tissue Engineeringmentioning
confidence: 99%
“…It was reported that there were about 31 million Americans who suffered from body defects [1]. Every year, there is globally an increasing number of patients suffering from various types of body defects caused by injuries and degenerative processes of various origin [2,3]. Critical defects require support for the growth of the cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasingly high requirement for information and intelligent technology, a great breakthrough has been made in material science, which is intelligent materials. The application of such materials has contributed to the development of modern intelligent instruments [ 1 , 2 ]. As functional materials applied in hydroacoustic sensing and image detection, 1-3 piezoelectric composites have become increasingly mature and play a central role in the sensitive elements of transducers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic impedance of the overall material gradually decreases with the increase in the volume ratio of the polymer phase, making the material easy to acoustically match with water or biological tissue. (2) The electromechanical coupling coefficient of thickness is large [29,31]. This condition is because the polymer separates each piezoelectric small column so that the transverse vibration mode of the composite is suppressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation